The Role of TMEM16A/ERK/NK-1 Signaling in Dorsal Root Ganglia Neurons in the Development of Neuropathic Pain Induced by Spared Nerve Injury (SNI) - Qinyi Chen; Liangjingyuan Kong; Zhenzhen Xu; Nan Cao; Xuechun Tang; Ruijuan Gao; Jingrong Zhang; Shiyu Deng; Chaoyang Tan; Meng Zhang; Yang Wang; Liang Zhang; et al. (Molecular Neurobiology, 2021)
Increasing evidence suggests that transmembrane protein 16A (TMEM16A) in nociceptive neurons is an important molecular component contributing to peripheral pain transduction. The present study aimed to evaluate the role and mechanism of TMEM16A in chronic nociceptive responses elicited by spared nerve injury (SNI). In this study, SNI was used to induce neuropathic pain. Drugs were administered intrathecally. The expression and cellular localization of TMEM16A, the ERK pathway, and NK-1 in the dorsal root ganglion (DRG) were detected by western blot and immunofluorescence. Behavioral tests were used to evaluate the role of TMEM16A and p-ERK in SNI-induced persistent pain and hypersensitivity. The role of TMEM16A in the hyperexcitability of primary nociceptor neurons was assessed by electrophysiological recording. The results show that TMEM16A, p-ERK, and NK-1 are predominantly expressed in small neurons associated with nociceptive sensation. TMEM16A is colocalized with p-ERK/NK-1 in DRG. TMEM16A, the MEK/ERK pathway, and NK-1 are activated in DRG after SNI. ERK inhibitor or TMEM16A antagonist prevents SNI-induced allodynia. ERK and NK-1 are downstream of TMEM16A activation. Electrophysiological recording showed that CaCC current increases and intrathecal application of T16Ainh-A01, a selective TMEM16A inhibitor, reverses the hyperexcitability of DRG neurons harvested from rats after SNI. We conclude that TMEM16A activation in DRG leads to a positive interaction of the ERK pathway with activation of NK-1 production and is involved in the development of neuropathic pain after SNI. Also, the blockade of TMEM16A or inhibition of the downstream ERK pathway or NK-1 upregulation may prevent the development of neuropathic pain.